Surviving online foreign language learning: the case for French language - Ismail, Saidah; Hassan @ Hussin, Omrah; Mohd Taib, Nor Azhar; Rahmat, Noor Hanim (Asian Economic and Social Society, 2021)
Similar to the learning of most languages, French language is initially learnt through a formal one-to-one classroom. However, the pandemic has given both teachers and students teaching/learning French as a foreign language to accept online learning as the new norm. The success of learning French language online depends on several factors. Both teachers and learners play different roles to make the lessons successful and meaningful. This study is done to investigate how online learning presence is influenced by learners’ motives to study a foreign language. This quantitative study is done to investigate how learners cope learning French online. 170 respondents were purposely chosen from learners who took French as a foreign language. The survey used has 49 items using 5-Likert scales. Findings revealed interesting information about online teaching and learning of foreign languages. The teacher anchors the online lesson with activities well planned and executed. The teacher takes the bulk of the responsibility to make online learning a success. Once the teacher’s and cognitive presence becomes positive, learners can begin to depend on their peers through social presence to maximise the learning experience.